The role of miR-17-1-3p in mitochondrial fusion gene expressions and muscle biogenesis with swimming exercise intervention in metabolic syndrome rat model - Karaman, Muhammed Emre; Tektemur, Ahmet; Perihan, Muhammed; Arslan, Cengiz; Gursu, Onur (Mattioli 1885, 2023)
Background and aim: it is known that exercise regulates the expression of mitochondrial fusion and muscle biogenesis involved genes. However, the mechanisms underlying the changes in mitochondrial fusion and muscle metabolism caused by exercise have not been clearly revealed yet. The aim of the study is to elucidate the molecular mechanisms of exercise therapy in metabolic syndrome. Methods: 21 Sprague-Dawley male rats were used in the study and by adding %30 fructose into drinking water Metabolic Syndrome (Mets) were induced after 5 weeks. The rats were randomly divided into 3 groups (Control, MetS, MetS+Exercise) as 7 rats in each cage after feeding for 5 weeks with 30% fructose diet. Swimming exercise were applied to the MetS+Exercise group for six weeks. Once the interventions were finished, the rats were decapitated and dissected to separate the skeletal muscle tissue samples. For the detection of alterations in the expression levels of MFN1, MFN2 and MSTN genes and miR-17-1-3p, the quantitative polymerase chain reaction (qPCR) was performed. Results: MFN1 and MFN2 expressions upregulated after exercise therapy in intervention group. MSTN and miR-17-1-3p were downregulated after exercise intervention. Conclusions: it has been shown in the present study, treating MetS with exercise therapy upregulates Mfn1 and Mfn2 gene expressions, which are involved in mitochondrial fusion dynamics, and that MSTN expression, which is increased in MetS, is downregulated by exercise intervention. To the best of our knowledge we demonstrated for the first time that exercise may regulates MSTN, Mfn1 and Mfn2 gene expressions by suppressing miR-17-1-3p. © Mattioli 1885.
Keywords: Exercise; Metabolic syndrome; MFN1; MFN2; miR-17-1-3p; MSTN